2016
DOI: 10.1109/tmi.2015.2505188
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Atlas Regression Forests: Multiple-Atlas-Based Automated Dose Prediction in Radiation Therapy

Abstract: Radiation therapy is an integral part of cancer treatment, but to date it remains highly manual. Plans are created through optimization of dose volume objectives that specify intent to minimize, maximize, or achieve a prescribed dose level to clinical targets and organs. Optimization is NP-hard, requiring highly iterative and manual initialization procedures. We present a proof-of-concept for a method to automatically infer the radiation dose directly from the patient's treatment planning image based on a data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 48 publications
1
66
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16] While the majority of these methods use hand-tailored or low dimensional features for prediction, recent advances in machine learning have spurred the development of KBP methods that predict full dose distributions using automatically generated high-dimensional features. 8,17,18 The most recent work in this space has focused on neural network-based KBP methods, which are trained on libraries of historical plans to predict dose for each axial slice separately [i.e., two-dimensional (2D) KBP methods] 8,18,19 or all slices concurrently [i.e., three-dimensional (3D) KBP methods]. 20,21 Among the 2D methods, generative adversarial networks (GANs) have been shown to perform the best 18 while among the 3D methods, DoseNet is considered state-of-the-art.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] While the majority of these methods use hand-tailored or low dimensional features for prediction, recent advances in machine learning have spurred the development of KBP methods that predict full dose distributions using automatically generated high-dimensional features. 8,17,18 The most recent work in this space has focused on neural network-based KBP methods, which are trained on libraries of historical plans to predict dose for each axial slice separately [i.e., two-dimensional (2D) KBP methods] 8,18,19 or all slices concurrently [i.e., three-dimensional (3D) KBP methods]. 20,21 Among the 2D methods, generative adversarial networks (GANs) have been shown to perform the best 18 while among the 3D methods, DoseNet is considered state-of-the-art.…”
Section: Introductionmentioning
confidence: 99%
“…Our model demonstrated that mean absolute errors of 3D dose for Body are 1.9 ± 1.8%. Using the atlas regression forests for three clinical treatment plan sites, McIntosh and Purdie reported that the overall dose prediction accuracies are 78.68%, 64.76%, 86.83% for whole breast, breast cavity, and prostate cases under the Gamma metric (passing rate standard is 5 mm/5%). Our study showed that the overall 3D passing rate for NPC cases ranged from 81.5% to 93.4% (averaged 88.4%) under the standard of 3 mm/3% (see Appendix ).…”
Section: Discussionmentioning
confidence: 99%
“…Improving specific components of an RT plan via knowledge-based techniques has been shown to substantially increase plan quality. 10,11,12 However, the implementation of such techniques with the goal of optimizing the RT plan as a whole would entail a paradigm shift in the manner in which cancer centers gather and store data. We conclude that a binary classification of erroneous plans remains the best feasible A natural extension of this work is to evaluate these methods across data from multiple institutions, although there are two key challenges.…”
Section: Discussionmentioning
confidence: 99%